TINJAUAN YURIDIS PEMBELAAN TERPAKSA (NOODWEER EXCESS) SEBAGAI DASAR PENGHAPUSAN PIDANA ANALISIS KASUS PELAKU BEGAL DI NTB YANG TERBUNUH OLEH KORBAN BEGAL AS - Isabella Merlin Anjani; Ade Adhari (UNES Law Review, 2023)
At this time, deviant behavior is widely found within society. Deviant behavior refers to actions that violate norms, rules, or laws in society. The research questions addressed in this study are: 1. What is the juridical perspective on perpetrators of robbery who are killed by victims due to self-defense (excessive self-defense)? 2. What is the legal certainty regarding self-defense (excessive self-defense) carried out by victims in response to robbery they experienced? The research method used in this Final Project is normative juridical research, which means that the issues raised, discussed, and elaborated in this study are focused on applying principles or norms within positive law. Excessive self-defense or exceeding the limits considered reasonable in self-defense occurs when someone goes beyond the boundaries deemed reasonable in a self-defense situation. In this case, although the robber may have initiated the attack or threatened the victim, the use of excessive force by the victim can raise questions about the legitimacy of their actions. In determining legal certainty in cases of self-defense, factors such as the force used, the level of threat to the victim, and the overall circumstances of the case will be examined by the court. Previous court decisions in similar cases or legal precedents can also influence legal certainty. Article 49, paragraph (1) of the Criminal Code highlights an important point, stating, "Defense against an attack or threat." Defense, in this context, must aim to stop actions or attacks deemed necessary at that moment. The defense must be proportionate to the encountered attack, and there must be no other means available to protect oneself except through self-defense.